2017
DOI: 10.2967/jnumed.116.183566
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Clinical SUV Ratio in Amyloid PET Imaging Using a Biomathematic Modeling Approach Toward the Efficient Development of a Radioligand

Abstract: Our study aimed to develop a method to mathematically predict the kinetic parameters K 1 (influx rate constant), k 2 (efflux rate constant), and BP ND (nondisplaceable binding potential) of amyloid PET tracers and obtain SUV ratios (SUVRs) from predicted timeactivity curves of target and reference regions. Methods: We investigated 10 clinically applied amyloid PET radioligands: 11 CPittsburgh compound B, 11 C-BF-227, 11 C-AZD2184, 11 C-SB-13, 18 F-FACT, 18 F-florbetapir, 18 F-florbetaben, 18 F-flutemetamol, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…The proposed screening methodology ( Fig. 1 ) consisted of the previously developed amyloid biomathematical model [8] ( Fig. 1 A), with population and noise simulations, and tracer evaluation based on CUI ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The proposed screening methodology ( Fig. 1 ) consisted of the previously developed amyloid biomathematical model [8] ( Fig. 1 A), with population and noise simulations, and tracer evaluation based on CUI ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the biomathematical model used in this study are found elsewhere [8] . We briefly summarize the model in predicting SUVR in the following sections.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations